Організація обліку загальновиробничих та адміністративних витрат на сільськогосподарських підприємствах - Павлова, Галина Євгеніївна; Pavlova, Halyna; Атамас, Олександр Петрович; Atamas Oleksandr; М. В. Осадча; M. Osadcha (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2024)
Слід зазначити, що стосується витрат на управління, то в бухгалтерському обліку до них належать адміністративні та загальновиробничі витрати. Ці витрати — це сукупність усіх витрат підприємства, які пов'язані з виробничи-ми процесами та з управлінською діяльністю. Хоча ці витрати не прямо впливають на цінність готової продукції, але їх відсутність може призвести до неможливості ведення діяльності. Таким чином, адміністративні та загальновиробничі витрати, як витрати на управління виробничих процесів, повинні бути своєчасно, повно і об'єктивно відображені в обліку. Визначено, що для ефективного обліку та розподілу загальновиробничих витрат сільськогосподарським підприємствам важливо враховувати специфіку галузі під час формування переліку субрахунків до рахунка 91, статей витрат, назв та складу загальновиробничих витрат, а також визначення нормальної потужності, методів і періодичностіїх розподілу та вибору бази для цього розподілу. Всі ці аспекти повинні бути задокументовані в наказі про облікову політику підприємства. The problem of accounting and distribution of general production costs becomes especially important for determining the total amount of costs and calculating the cost of production. In the modern conditions of adaptation of accounting and tax accounting, it is necessary to substantiate these issues, which leads to the need to develop an accounting policy of the enterprise regarding the accounting and distribution of general production costs. Features of accounting and distribution of these costs at enterprises of various industries are of great scientific interest, as many questions remain unsolved. As for management costs, in accounting they include administrative and general production costs. These costs are the totality of all costs of the enterprise, which are related to production processes and management activities. Although these costs do not directly affect the value of finished products, their absence can lead to the impossibility of conducting business. Fixed overhead costs are allocated to each cost object using an allocation base (such as labor hours, wages, output, or direct costs) based on normal production capacity. The amount of this capacity is determined by the enterprise and specified in the Order on accounting policy. Administrative costs are, by definition, period costs. Therefore, it is important to correctly and timely attribute these costs to a specific reporting period. Before recognizing administrative expenses, it is necessary to determine whether the entity received all the benefits from the expenses in this reporting period. For example, if an annual subscription to the newspaper "All About Accounting" was purchased, these costs should be considered costs of future periods and recorded on account 39 "Expenses of future periods». For effective accounting and distribution of general production costs to agricultural enterprises, it is important to take into account the specifics of the industry when forming a list of sub-accounts to account 91, cost items, names and composition of general production costs, as well as determining the normal capacity, methods and periodicity of their distribution and choosing the basis for this distribution.
Organization of accounting of general production and administrative costs in agricultural enterprises
Keywords: організація; organization; облік; accounting; загальновиробничі витрати; general production costs; сільськогосподарське підприємство; agricultural enterprise